Stakeholder Coordination in the Tokwe - Mukosi Disaster Response in Masvingo Province, Zimbabwe - Zikhali, Whitehead (Advances in Social Sciences Research Journal, 2018)
Physical displacement and natural disasters have occurred in Zimbabwe since pre-independence times, always posing a threat to human life and developmental gains. Disasters in the form of flooding continuously contribute to loss in human lives, destruction of shelter, damage to household assets and in internal displacement. In 2014, a combination of high rainfall and damages on the Tokwe-Mukosi dam wall contributed to flooding of communities in close proximity to the dam. The disastrous outcome was the flooding of the immediate catchment area which communities were unable to cope with. The government sought for assistance from disaster management actors during and after the flood with mixed response. This paper explores roles played by stakeholders in responding to flooding of Tokwe-Mukosi dam in Masvingo Province. Data for this paper was collected through structured interviews, observations and focus group discussions. Relying on ‘habitus’ and ‘pastoral power’ as conceptual tools, the paper broadly found out that communities resorted to various reservoirs of knowledge and experience to limit their post-disaster vulnerabilities while also demonstrating abilities to negotiate various power structures. Finally, the paper recommends that the interventions from various agencies recognise the agency of displaced actors in attempting to alleviate challenges. In addition, researchers ought to equally embrace more innovative methods and conceptual lens when exploring social phenomena in order to go beyond narrow narrative approaches and developmentalist discourses.